Poetry is not born from multicultural values vacuity: A Hermeneutical Analysis - Muliadi, Muliadi; F. Amin, Kasma; Rabiah, Sitti; Kaharuddin, Kaharuddin; Hasyim, Muhammad (Research Journal in Advanced Humanities, 2023)
The purpose of this research is to reveal the values of poetry from behind the words used by the poet. Data and data sources are taken from Husni Djamaluddin's (AP-HD) poem entitled. Data sources and data are read repeatedly and deeply. After that, codification and classification were carried out to understand the meaning semantically, reflexively, and existentially in accordance with Paul Ricoeur's hermeneutic theory. The method used in the research is the hermeneutic method. The hermeneutic method used is Paul Ricoeur's hermeneutic with the following working steps: (1) the symbolic step or understanding from symbol to symbol, (2) the step of giving meaning by symbols and careful exploration of meaning, (3) a truly philosophical step, namely thinking by using symbols as a starting point. These three steps are closely related to the steps of language understanding, namely semantic, reflexive, and existential or ontological. In this study, it was found that the aspect of love in the poem "Senyum dan Dendam", the aspect of hope in the poem "Jangan Kau Katakan Jangan", and the aspect of exemplary in the poem "Salib" in Husni Djamaluddin's poetry collection, Indonesia Masihkah Engkau Tanah Airku? Theoretically, this research can be a model of multicultural value research by utilizing poetry texts as data and data sources; practically, it can be utilized as an analysis model, both for students and for teachers; socially, it can provide enlightenment for its readers that poetry contains very valuable values in life.